Sleep quality in older adults with arterial hypertension - Leonel, Adela Alba; Sánchez Piña, Sofía; Papaqui Alba , Samantha; Montes Rodríguez, Brandon Gerardo (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Introduction: Poor sleep could be the cause of high blood pressure and other chronic diseases. Objective: To know the quality of sleep of people with arterial hypertension. Methodology: A descriptive study were carried out; the Pittsburgh Sleep Quality Index questionnaire was applied. Results: The quality of sleep was evaluated in 85 people with arterial hypertension, from April to December 2021. 84% have an index of poor and very poor quality of sleep. Conclusion: People with hypertension with poor and very poor quality of sleep can affect their blood pressure